Enterprise 2.0 – Is The Market Ready? - Dragos Marian Mangiuc (Journal of Accounting and Management Information Systems (JAMIS), 2011)
Enterprise 2.0 family technologies have growing popularity, the cloud computing market is growing rapidly and, as a consequence, companies of all sizes start to evaluate the potential fit. The use of "Software as a Service", "Platform as a Service" and "Infrastructure as a Service" has been evolving during the past years and has become increasingly popular. As its computing viability and benefits are legitimized, the adoption rate is rapidly increasing. The most popular business model in the abovementioned family is by far "Software as a Service" (also called SaaS), which is a software distribution model assuming the software applications are hosted and maintained by the vendor or the distributor, and user access is granted exclusively by means of the Internet. Based on both literature review and action research, the paper at hand is a synthesis for the results of an empirical study performed during the last two years among Romanian and foreign companies, in order to outline and provide an objective and unbiased answer to the question: "Is the market ready for these technologies or did they come too soon?". The paper is a part of a larger research performed by the author in the field of Enterprise 2.0 technologies.
Keywords: M15; 650; Enterprise 2.0; Software as a Service; Platform as a Service; Infrastructure as a Service; Empirical study